Age- and Sex-Related Differences in the Maximum Muscle Performance and Rate of Force Development Scaling Factor of Precision Grip Muscles - Corrêa, Talyene G C; Donato, Stephanie V S; Lima, Kauê C A; Pereira, Ronaldo V; Uygur, Mehmet; de Freitas, Paulo Barbosa (Motor control, 2020)
The aim of this study was to explore the effects of age and sex on the rate of force development scaling factor (RFD-SF) and maximum performance (i.e., maximum grip force [GFMax] and maximum rate of grip force development [RGFDMax]) of precision handgrip muscles. Sixty-four subjects, allocated in four groups according to their age and sex, were asked to hold an instrumented handle with the tip of the digits and perform two tests: maximum voluntary contraction and RFD-SF tests. In the maximum voluntary contraction test, GFMax and RGFDMax were assessed. In the RFD-SF test, the subjects generated quick isometric force pulses to target amplitudes varying between 20% and 100% of their GFMax. The RFD-SF and R2 values were obtained from the linear relationship between the peak values of the force pulses and the corresponding peak values of the rate of force development. Younger adults and males produced higher GFMax and RGFDMax and presented higher R2 and RFD-SF than older adults and females, respectively. No correlations between GFMax and RFD-SF and between RGFDMax and RFD-SF were observed.